Inhibiting Sphingosine 1-Phosphate Receptor Subtype 3 Attenuates Brain Damage During Ischemia-Reperfusion Injury by Regulating nNOS/NO and Oxidative Stress - Fan, Xuehui; Chen, Hongping; Xu, Chen; Wang, Yingju; Yin, Pengqi; Li, Meng; Tang, Zhanbin; Jiang, Fangchao; Wei, Wan; Song, Jihe; Li, Guozhong; Zhong, Di (Frontiers in Neuroscience, 2022)
Background Ischemic stroke (IS) is a common disease endangering human life and health. Cerebral ischemia triggers a series of complex harmful events, including excitotoxicity, inflammation and cell death, as well as increased nitric oxide production through the activation of nitric oxide synthase (NOS). Oxidative stress plays a major role in cerebral ischemia and reperfusion. Sphingosine 1-phosphate receptor subtype 3 (S1PR3), a member of S1P’s G protein-coupled receptors S1PR1-S1PR5, is involved in a variety of biological effects in the body, and its role in regulating oxidative stress during cerebral ischemia and reperfusion is still unclear. Methods Transient middle cerebral artery occlusion (tMCAO) mice were selected as the brain ischemia–reperfusion (I/R) injury model. Male C57/BL6 mice were treated with or without a selective S1PR3 inhibition after tMCAO, and changes in infarct volume, Nissl staining, hematoxylin-eosin (H&E) staining and NOS protein, nitric oxide (NO), superoxide dismutase (SOD), and malondialdehyde (MDA) content after tMCAO were observed. Results In the cerebral ischemia–reperfusion model, inhibition of S1PR3 improved the infarct volume and neuronal damage in mice after tMCAO. Similarly, inhibition of S1PR3 can reduce the expression of NO synthase subtype neuronal NOS (nNOS) and reduce the production of NO after cerebral ischemia. After cerebral ischemia and reperfusion, the oxidative stress response was enhanced, and after the administration of the S1PR3 inhibitor, the SOD content increased and the MDA content decreased, indicating that S1PR3 plays an important role in regulating oxidative stress response. Conclusion Inhibiting S1PR3 attenuates brain damage during I/R injury by regulating nNOS/NO and oxidative stress, which provides a potential new therapeutic target and mechanism for the clinical treatment of IS.